2019
DOI: 10.1177/0890334419848414
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Application-Based Breastfeeding Education for Physicians and Nurses: A Scoping Review

Abstract: Background: Physicians and nurses are expected to support breastfeeding mothers. However, there is a lack of standardized lactation education throughout training programs and hospitals. As a result, providers lack the necessary confidence and skills to guide mothers throughout the breastfeeding experience. The hands-on nature of breastfeeding management demands the implementation of application-based learning tools to improve skills retention and patient breastfeeding outcomes. Research aim: In this scoping re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 38 publications
0
20
0
1
Order By: Relevance
“…A recent scoping review of application-based breastfeeding education for nurses and physicians demonstrated a variety of teaching methods using real patients and roleplay, but found no standardised method of educational intervention or evaluation [38]. Several teaching methods have been suggested to provide an integrated breastfeeding education for the undergraduate medical student.…”
Section: Improving Breastfeeding Educationmentioning
confidence: 99%
“…A recent scoping review of application-based breastfeeding education for nurses and physicians demonstrated a variety of teaching methods using real patients and roleplay, but found no standardised method of educational intervention or evaluation [38]. Several teaching methods have been suggested to provide an integrated breastfeeding education for the undergraduate medical student.…”
Section: Improving Breastfeeding Educationmentioning
confidence: 99%
“…Low maternal breastfeeding self-efficacy and inadequate lactation support from healthcare providers are key reasons for premature breastfeeding cessation [1][2][3]. Insufficient clinical education in lactation support is a longstanding problem across healthcare specialties, professions, and levels of training [4][5][6][7][8][9][10][11]. Most physicians and nurses do not feel confident in their ability to support families with breastfeeding initiation or maintenance [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization strongly recommends the use of "high-fidelity" (realistic) simulation for health professional education because it leads to greater acquisition, retention, and transfer of technical and non-technical skills [17]. Low-fidelity commercially-available or handmade cloth breast models are frequently used in breastfeeding education, but the approach is not standardized and learning and patient outcomes are rarely assessed [5,11,12]. We propose that high-fidelity simulation is the ideal learning modality for breastfeeding education for three reasons: 1) Lactation support requires deliberate practice and confidence in examining, touching, and moving breast tissue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These new family structures have increased in recent years, thereby increasing rates of breastfeeding due to lactation being induced (Schnell, 2015), although women who adopt a child, who have a child through surrogacy, or who are the non-pregnant partners in a lesbian couple, may be able to breastfeed. However, it has been reported that many of these new family structures have found a lack of support during the process from nurses and physicians (Chuisano & Anderson, 2019).…”
Section: Introductionmentioning
confidence: 99%